Psychoanalytic Play Therapy as Psychotherapy in Children - Sumarni (Scientia Psychiatrica, 2020)
Play therapy is a form of psychotherapy that can be used in children. Play therapy does not only recognize environmental factor but also promote parent guidance and school consultation as important functions of the child therapist. This article aimed to understand psychoanalytic therapy as a way to help the child to suffer less, relieve anxiety, cope with trauma, be better able to attend, learn and work in school, manage personal anger and aggression; and come to terms with a learning disability or physical handicap. The role of the therapist in psychotherapy was very important. The therapist and his attitude were a form of intervention. Most of all, the therapist empathically listens and responds to the child. Parent guidance in the therapeutic process was more effective. The parent-child relationship was an as significant factor in the effectiveness of play therapy.